Effects of Artificial Intelligence on People and Organization (Architecture Image Studies, 2025)
Artificial intelligence is one of the widely used digital technology, which has laid the foundations for digital transformation in companies and has changed the traditional landscape of businesses. AI is a broad field, which consists of several other technologies like machine learning, deep learning, artificial neural networks, etc. and enables the people or organizations to rethink and re-establish their innovative solutions and existing decision-making processes. On the other hand, AI is being used in several domains such as healthcare, business, manufacturing, education, etc. providing numerous societal and economic benefits to the individuals. The organizations that use AI-based solutions. AI-empowered solutions help business organisations to gain a competitive edge in the market by improving their service quality and customer satisfaction. AI also helps the organizations in resolving technical, developmental and other issues related to service delivery as well as providing recommendations to protect human and business values. To cover all these aspects related to AI, the current study is emphasized by exploring its effects on people and organizations. The main reason behind conducting this study is to establish a deep understanding of the subject matter so that companies and individuals can have a deep understanding of the dark side of AI involving over the years. To achieve the objectives of the current research, a theoretical examination is performed, in which a review-based analysis is conducted with the help of several secondary sources of information. For carrying out this examination in an effective manner, various digital repositories such as MDPI, research gate, science direct, UNSW Library etc. are used, which include various relevant academic sources of information. Using a keyword-based approach, the most relevant studies required to perform this task are collected and reviewed thematically. As per the reviewed papers, it is found that AI's dark sides are either unnoticed or overlooked because of the overwhelmed benefits. However, the negative impacts on individuals and organizations cannot be ignored. It found that the AI involved has drastically replaced the humans in many organizations which led to the situation of unemployment, made the humans lazy and inactive, over-dependency which decreased interpersonal interaction and social support from the use of electronic performance monitoring systems (Carayon, 1993). Meanwhile, the psychological effects on individuals such as computer anxiety (Heinssen et al., 1987) digitization of communications introduced new security threats as data transmitted on electronic devices or networks becomes susceptible to third-party interception and breaches, sometimes unnoticed.Also, the harmfulness of technostress and IT on IT users have become more evident since IT has transmuted into a major component of humans’ job routines and private lives (Henri Pirkkalainen, Markus Salo. 2016).